Pemmali dalam Mitos Kepercayaan Masyarakat Bugis Sidenreng Rappang - Arun Sanjaya; Andi Agussalim Aj; Andi Fatimah Junus (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. This study aims to describe the form and meaning of pemmali in the myth of the beliefs of the Bugis sidenreng rappang people. This research is a type of qualitative research in descriptive form. The data in this study is oral data in the form of words, containing pemmali which is believed by the Bugis Sidenreng Rappang community. Data collection is carried out by observation, interview and documentation techniques. Based on the results of research and data analysis, it was found that the form and meaning contained in Pemmali (1) Pemmali that has cause and effect, (2) Pemmali who has no cause and effect. Keywords: Pemmali, Myth, Bugis Society